2006
DOI: 10.1242/dev.02206
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation ofmummyis needed for apical extracellular matrix formation and epithelial morphogenesis inDrosophila

Abstract: Many epithelia produce apical extracellular matrices (aECM) that are crucial for organ morphogenesis or physiology. Apical ECM formation relies on coordinated synthesis and modification of constituting components, to enable their subcellular targeting and extracellular assembly into functional matrices. The exoskeleton of Drosophila, the cuticle, is a stratified aECM containing ordered chitin polysaccharide lamellae and proteinaceous layers, and is suited for studies of molecular functions needed for aECM asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 53 publications
4
61
0
1
Order By: Relevance
“…One line, 2L0058, showed a convoluted dorsal trunk. We therefore tested it for complementation of mutations in known genes on the second chromosome that show this mutant phenotype Âœconvoluted, varicose, nervana2 (Beitel and Krasnow 2000), and mummy (cystic) (Araujo et al 2005;Tonning et al 2006) but found it not to be allelic to any of them. However, the observation that a line from phenotypic class A had a convoluted dorsal trunk suggested that other lines from this class might also have such a phenotype and be allelic to the genes mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…One line, 2L0058, showed a convoluted dorsal trunk. We therefore tested it for complementation of mutations in known genes on the second chromosome that show this mutant phenotype Âœconvoluted, varicose, nervana2 (Beitel and Krasnow 2000), and mummy (cystic) (Araujo et al 2005;Tonning et al 2006) but found it not to be allelic to any of them. However, the observation that a line from phenotypic class A had a convoluted dorsal trunk suggested that other lines from this class might also have such a phenotype and be allelic to the genes mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Tube expansion and extension relies on a luminal chitin filament that assembles transiently in the tracheal tubes (reviewed in Swanson and Beitel, 2006). The metabolic pathway that leads to chitin synthesis involves several enzymes, among which are Mmy and Kkv (Araujo et al, 2005;Devine et al, 2005;Tonning et al, 2006;Tonning et al, 2005). In addition, other proteins are known to participate in the proper assembly and/or modification of the chitin filament, such as Knk, Rtv , Verm and Serp (Luschnig et al, 2006;Wang et al, 2006).…”
Section: Ttk In Tube Sizementioning
confidence: 99%
“…Glycosylation plays a variety of roles during development, including signal transduction, morphogen distribution, extracellular matrix (ECM) formation, and cell-cell and cell-ECM interactions (Haltiwanger 2002;Baeg et al 2004;Tonning et al 2006). For example, Fringe-dependent glycosylation modifies the affinity of Notch for various ligands differently.…”
Section: Introductionmentioning
confidence: 99%